Energy Systems Contribution in the Running-based Anaerobic Sprint Test - Milioni, F.; Zagatto, A. M.; Barbieri, R. A.; Andrade, V. L.; dos Santos, J. W.; Gobatto, C. A.; da Silva, A. S. R.; Santiago, P. R. P.; Papoti, M. (International Journal of Sports Medicine, 2017)
The aims of the present study were to verify the contributions of the energy systems during repeated sprints with a short recovery time and the associations of the time- and power-performance of repeated sprints with energetic contributions and aerobic and anaerobic variables. 13 healthy men performed the running-based anaerobic sprint test (RAST) followed by an incremental protocol for lactate minimum intensity determination. During the RAST, the net energy system was estimated using the oxygen consumption and the blood lactate responses. The relative contributions of oxidative phosphorylation, glycolytic, and phosphagen pathways were 38, 34, and 28%, respectively. The contribution of the oxidative pathway increased significantly during RAST especially from the third sprint, at the same time that power- and time-performances decreases significantly. The phosphagen pathway was associated with power-performance (peak power=432±107 W, r=0.65; mean power=325±80 W, r=0.65; minimum power=241±77 W, r=0.57; force impulse=1 846±478 N·s, r=0.74; p<0.05). The time-performance (total time=37.9±2.5 s; best time=5.7±0.4 s; mean time=6.3±0.4 s; worst time=7.0±0.6 s) was significantly correlated with the oxidative phosphorylation pathway (0.57<r+>+0.65; p<0.05) and glycolytic pathway (0.57+<+r>0.58; p<0.05). The oxidative pathway appears to play an important role in better recovery between sprints, and the continued use of the glycolytic metabolic pathway seems to decrease sprint performances. Finally, the phosphagen pathway was linked to power production/maintenance.
Keywords: oxygen uptake; bood lactate; aerobic metabolism; anaerobic metabolism; physiological effort; performance